Pharmacogenetic impact of SLC22A1 gene variant rs628031 (G/A) in newly diagnosed Indian type 2 diabetes patients undergoing metformin monotherapy. Issue 3 (9th April 2023) - Singh, Shalini; Shukla, Ashwin Kumar; Usman, Kauser; Banerjee, Monisha
Abstract : Objectives: Type 2 diabetes (T2D) imposes an enormous burden all over the world in both developed and developing countries. Inter-individual differences are attributed to polymorphisms in candidate genes resulting in altered absorption, transportation, distribution, and metabolism of oral antidiabetic drugs (OADs). Hence, the present study was undertaken to evaluate the pharmacogenetic impact of SLC22A1 gene variant rs628031 (G/A) on metformin monotherapy in newly diagnosed untreated T2D patients. Methods: Newly diagnosed T2D patients ( n  = 500) were enrolled according to inclusion/exclusion criteria. Initially, enrolled subjects were prescribed metformin monotherapy and followed up for at least 12 weeks. Response to metformin was evaluated in 478 patients who revisited for follow-up by measuring HbA1c. Result: Out of 478 patients, 373 were responders to metformin monotherapy while 105 were non-responders. The pharmacogenetic impact was evaluated by genotype, haplotype, and pharmacogenetic analyses. 'GG' genotype and 'G' allele of SLC22A1 rs628031 G/A were observed in 48.8% and 67.7% of Met responders, respectively, while 20.9% and 49.1 % were in non-responders. Therefore, there was a 2.18-fold increase in the success rate of Met therapeutics. Conclusion: Individuals carrying the 'GG' genotype or 'G' allele for SLC22A1 gene variant rs628031 G/A are better responders for Metformin monotherapy.